DEVELOPMENT OF THE CONTROL SYSTEM REGARDING THE SPREAD OF INFECTIOUS DISEASES IN THE RUSSIAN EMPIRE BE-FORE THE TWENTIETH CENTURY - Anatolii Hrynzovskyi (Bogomolets National Medical University, 2020)
In this paper we considered the establishment and development of na-tional and local authorities, whose task was to provide and implement a na-tional policy for the prevention of the emergence and spread of infectious diseases. We studied the powers of state and local governments in the structure of the control system of the spread of infectious diseases in the Russian Em-pire until the early twentieth century. Shown is the relative impact of the development of medical science, in-ternational trade on the adoption of international sanitary conventions and the development of new legal documents in the field of preventive medicine, and their implementation in the structure of the legislation of the Russian Empire. The value of rural and urban reforms (1864) for the development of preventive medicine. Creation of the conditions for the formation in the structure of local government professional institutions responsible for the sanitation and anti-epidemic work at the territorial (rural and urban) level, as well as with provincial governments and the central government. It is shown that with the creation of new forms of self-governing, ways of developing infection control in rural and urban medicine are relatively dif-ferent, primarily, to the specific conditions of life and labor of the rural and urban populations, as well as to the severity of the actions of those risk fac-tors which influenced the sanitary-epidemiological welfare of the population.